THE ROLE OF A LAWYER IN THE CONCLUSION OF A SETTLEMENT AGREEMENT IN ECONOMIC COURTS - Tollibayeva Malika Ulmasjon Kizi (International Journal of Business, Law and Political Science, 2025)
Objective: This study examines the status, obligations, and practical roles of lawyers in preparing settlement agreements in economic courts, with a focus on how they protect party interests and contribute to efficient dispute resolution. Method: Using a qualitative legal analysis that integrates national legislation, international practices, and documented case examples, the study evaluates the legal authority of lawyers and their involvement in alternative dispute resolution mechanisms. Results: The findings show that lawyer-led settlement agreements promote economic stability, increase trust among business entities, reduce the workload of courts, and enhance the efficiency of economic dispute resolution. The analysis also indicates that strengthening the legal powers and ethical responsibilities of lawyers can further improve the quality and enforceability of settlements. Novelty: This research offers evidence-based recommendations that emphasize the strategic role of lawyers not merely as representatives but as proactive facilitators of settlement, highlighting the institutional value of bar associations in shaping modern dispute resolution practices.